On some generalized difference sequence spaces and related matrix transformations - Çolak, Rifat; Et, Mikail (My University, 1997)
In this paper we introduce ?-duals and ?-duals of the sequence spaces l?(?m), c(?m), (m ? N) where for instance l?(?m) = (x = (xk): (?mxk)?l?), and we characterize some matrix classes related with these sequence spaces. This study generalizes some results of Kızmaz[4] in special cases. © 1997 by the University of Notre Dame. All rights reserved.
Keywords: Difference sequences; Matrix transformations; ?-dual; ?-dual